Integrated Information Systems and Management Accounting System Design: A Global Bibliometric Analysis of Their Impact on Interorganizational Performance - Zahra, Silmy Auliya (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study examines the role of the Management Accounting System (MAS) in supporting interorganizational performance through Integrated Information Systems (IIS). Using a bibliometric analysis approach on global publications, the research explores trends, core themes, and the relationships among MAS, IIS, and interorganizational performance. The results indicate a significant increase in publications related to this topic since 2007, with prominent focuses such as cost accounting, competition, decision-making, and accounting. The integration of IIS and MAS has been shown to enhance efficiency, coordination, and transparency within interorganizational relationships, as well as to support strategic decision-making. The study also identifies learning systems and organizational learning as areas that require further exploration.